Vulnerable by Design: Black Theology as Prophetic Theology - Fortein, Eugene (The ecumenical review, 2022)
The COVID-19 pandemic plunged vulnerable populations and the church in South Africa into a crisis. This article argues that the situation of poor and vulnerable people is not an accident but a deliberate design of the powerful and is therefore closely linked to South Africa’s political past. The paper traces the origins of structural vulnerabilities in various apartheid laws, including the Native Land Act, the Group Areas Act, and the Bantu Education Act. It argues that this deliberate shaping of vulnerable groups continues in post-apartheid South Africa – hence, South Africa has evolved from a racialized society to a market-based society. Finally, the article concludes that the COVID-19 pandemic offers a kairos moment for the church in South Africa to redesign its theologies and consider an option for Black theology as prophetic theology.